2017
DOI: 10.21037/jgo.2016.12.03
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of adenosquamous esophageal carcinoma

Abstract: Background: Current published information of adenosquamous carcinoma (ASC) of the esophagus in the United States is limited to isolated case reports. We sought to study the clinical characteristics of this tumor using the Surveillance, Epidemiology and End Results (SEER) database.Methods: Relevant data of all patients with esophageal cancer in the SEER database diagnosed from 1998-2010 was obtained. Demographic, grade, stage, treatment and survival characteristics of patients with ASC were summarized and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 15 publications
1
48
1
Order By: Relevance
“…Patients with ASC had worse OS compared to ACA, but not ESCC in both univariate and multivariate analyses (OR=0.76; Scale bar, A, B, E, F, 500 μm, C, D, G, H, 100 FOXA1 expression and patients' overall survival. For A, age<61 years old, B, middle esophagus, C, non-lymph node metastasis. p<0.05 and OR=0.86; p<0.05 respectively) [27]. GECEC had no glands compared to ASC, but had worse OS compared to ESCC patients, suggesting that GECEC may be a subtype of esophageal cancer with poor prognosis.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients with ASC had worse OS compared to ACA, but not ESCC in both univariate and multivariate analyses (OR=0.76; Scale bar, A, B, E, F, 500 μm, C, D, G, H, 100 FOXA1 expression and patients' overall survival. For A, age<61 years old, B, middle esophagus, C, non-lymph node metastasis. p<0.05 and OR=0.86; p<0.05 respectively) [27]. GECEC had no glands compared to ASC, but had worse OS compared to ESCC patients, suggesting that GECEC may be a subtype of esophageal cancer with poor prognosis.…”
Section: Discussionmentioning
confidence: 87%
“…The functions and meanings of the GECEC are not clear. Adenosquamous esophageal carcinoma (ACS) is another esophageal cancer subtype, a rare histological variant comprising 1% of esophageal adenocarcinoma (ACA) in the Unites States [27]. Patients with ASC had worse OS compared to ACA, but not ESCC in both univariate and multivariate analyses (OR=0.76; Scale bar, A, B, E, F, 500 μm, C, D, G, H, 100 FOXA1 expression and patients' overall survival.…”
Section: Discussionmentioning
confidence: 99%
“…In patient series from both Asia[ 3 , 4 , 5 , 6 , 7 ] and the US,[ 8 , 9 ] the reported incidence rates range between 0.37%[5] and 1%. [ 3 , 7 , 9 ] The age and gender distribution is also consistent throughout the literature. ASC mostly presents in people older than 40 years, with incidence peaking around the 7th decade of life.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies have shown dysphagia to be the most common presenting symptom of ASC, followed by retrosternal or upper abdominal pain and weight loss. [ 3 , 5 , 6 , 9 , 25 ]…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation